Isoprinosine as a foot-and-mouth disease vaccine adjuvant elicits robust host defense against viral infection through immunomodulation - Kim, Hyeong Won; Ko, Mi-Kyeong; Shin, Seokwon; Park, So Hui; Park, Jong-Hyeon; Kim, Su-Mi; Lee, Min Ja (Frontiers in Cellular and Infection Microbiology, 2024)
Commercial foot-and-mouth disease (FMD) vaccines have limitations, such as local side effects, periodic vaccinations, and weak host defenses. To overcome these limitations, we developed a novel FMD vaccine by combining an inactivated FMD viral antigen with the small molecule isoprinosine, which served as an adjuvant (immunomodulator). We demonstrated isoprinosine-mediated early, mid-term, and long-term immunity through in vitro and in vivo studies and complete host defense against FMD virus (FMDV) infection through challenge experiments in mice and pigs. We also elucidated that isoprinosine induces innate and adaptive (cellular and humoral) immunity via promoting the expression of immunoregulatory gene such as pattern recognition receptors [PRRs; retinoic acid-inducible gene (RIG)-I and toll-like receptor (TLR)9], transcription factors [T-box transcription factor (TBX)21, eomesodermin (EOMES), and nuclear factor kappa B (NF-κB)], cytokines (IL-12p40, IL-23p19, IL-23R, and IL-17A), and immune cell core receptors [cluster of differentiation (CD)80, CD86, CD28, CD19, CD21, and CD81] in pigs. These findings present an attractive strategy for constructing novel FMD vaccines and other difficult-to-control livestock virus vaccine formulations based on isoprinosine-induced immunomodulatory functions.